Choice of management strategy for colorectal cancer based on a diagnostic immunohistochemical test for defective mismatch repair. Issue 3 (1st September 1999) - Cawkwell, L; Gray, S; Murgatroyd, H; Sutherland, F; Haine, L; Longfellow, M; O'Loughlin, S; Cross, D; Kronborg, O; Fenger, C; Mapstone, N; Dixon, M; et al.
Abstract : BACKGROUND: Despite intensive research into the molecular abnormalities associated with colorectal cancer (CRC), no diagnostic tests have emerged which usefully complement standard histopathological assessments. AIMS: To assess the feasibility of using immunohistochemistry to detect replication error (RER) positive CRCs and determine the incidence of RER positivity within distinct patient subgroups. METHODS: 502 CRCs were analysed for RER positivity (at least two markers affected) and/or expression of hMSH2 and hMLH1. RESULTS: There were 15/30 (50%) patients with metachronous CRCs, 16/51 (31%) with synchronous CRCs, 14/45 (31%) with a proximal colon carcinoma, and 4/23 (17%) who developed a CRC under the age of 50 showed RER positivity. However, 0/54 patients who developed a solitary carcinoma of the rectum/left colon over the age of 50 showed RER positivity. Immunohistochemical analysis revealed that 66/66 (100%) RER positive carcinomas were associated with complete lack of expression of either hMSH2 or hMLH1. This correlation was confirmed using a further 101 proximal colon carcinomas. Patients with a mismatch repair defective carcinoma showed improved survival but a 5.54 times relative risk of developing a metachronous CRC. A prospective immunohistochemical study revealed 13/117 (11%) patients had a mismatch repair defective carcinoma. A fivefold excess of hMLH1 defective cases was noted. CONCLUSIONS: All RER positive carcinomas were identified by the immunohistochemical test. This is the first simple laboratory test which can be performed routinely on all CRCs. It will provide a method for selecting patients who should be investigated for HNPCC, offered long term follow up, and who may not respond to standard chemotherapy regimens.